Increasing Motivation and Teamwork to Encourage Services for Posyandu Cadres in the City of Pematang Siantar - Marto Silalahi; Ady Inrawan; Juan Anastasia Putri; Kevin Indajang; Acai Sudirman (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
Teamwork in the organization is considered crucial to encourage continuous performance improvement. Teamwork will become a driving force that has energy and synergy for individuals who are members of teamwork. Communication will run well based on awareness of the responsibilities of each member. The purpose of implementing this service is to help those who need understanding and practice implementing effective teamwork when providing services to the community. Partners are posyandu cadres in the Kahean Village with the address Jl. Tualang, No. 28, Kel. Kahean, Kec. North Siantar. The stages of implementing this event include the opening and introduction of solid teamwork, an explanation of teamwork, and a presentation on some of the problems that Posyandu cadres often face when providing services to the community, then continued discussions on building and developing service quality based on teamwork aspects. After the community service activities are completed, follow-up interviews are conducted regarding the impact of the community service activities. In accordance with the results of the interviews, it is known that the understanding of Posyandu cadres related to an increase in motivation in communication increased by 80%, and the work and implementation of solid teamwork increased by 90%.